THE EFFECT OF ACCELERATED LEARNING MODEL ON MOTIVATION AND MATHEMATICS LEARNING OUTCOMES OF STUDENTS OF CLASS VII MTsN 1 PASAMAN BARAT - Rizka Yulia; Isnaniah (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
This research is motivated by the problems found in class VII MTsN 1 Pasaman Barat that students' motivation is low in learning, and student learning outcomes are still below the KKM.This study aims to determine whether the Accelerated Learning learning model has an effect on student motivation and learning outcomes in class VII MTsN 1 Pasaman Barat in the 2021/2022 school year. This research is a type of pre-experimental research with the research design of The Static Group Comparison Design. The results showed that the students' motivation to learn mathematics was processed using the t-test at a significant level = 0.05, the t-count t-table value was 1.68 and using Minitab software the P-Value = 0.020 = 0.05 so that H0 was rejected. and H1 is accepted. So, it can be concluded that the Accelerated Learning learning model has a significant effect on the learning motivation of class VII MTsN 1 Pasaman Barat students in the 2021/2022 academic year. Students' mathematics learning outcomes were processed using the t-test at a real level = 0.05, the value of tcount ttable was 1.68 and from Minitab Software calculations obtained P-Value = 0.010 = 0.05 so that H0 was rejected and H1 was accepted. So, it can be concluded that the Accelerated Learning learning model has a significant effect on the learning outcomes of class VII MTsN 1 Pasaman Barat students in the 2021/2022 academic year.